Pengaruh Penerapan Total Quality Management terhadap Kinerja Inovasi Dimediasi Knowledge Sharing - Jostein Frandelli; Anita Silvianita (SAFE-Network, 2023)
To be able to compete and survive in all conditions, every company pays great attention to the maintenance of human resources as a company effort to obtain an effective strategy that aims to support the company's success in achieving its goals. This research was conducted to determine the effect of implementing total quality management (TQM) on innovation performance through knowledge sharing as an intervening variable at Auto 2000 Soekarno Hatta 145 Bandung. This research uses a quantitative method with a descriptive-causality research type. As for sampling, it was carried out using the saturated sampling technique method, with a total of 70 respondents. The data analysis technique used in this study is descriptive analysis and the Partial Least Square-Structural Equation Model (PLS-SEM) assisted by the Smart PLS 3.0 analysis tool. The results of this research indicate that there is a positive and significant relationship between total quality management (TQM) and innovation performance, total quality management (TQM) and knowledge sharing, knowledge sharing and innovation performance, as well as an indirect relationship between total quality management (TQM) on innovation performance through knowledge sharing. So that in an effort to improve employee innovation performance, the application of total quality management (TQM) and knowledge sharing needs to be evaluated and improved at Auto 2000 Soekarno Hatta 145 Bandung.